2005
DOI: 10.4049/jimmunol.175.4.2475
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Interacting Chromosome Loci Control Disease Susceptibility in Murine Model of Spondyloarthropathy

Abstract: Autoimmune spondylitis was induced in BALB/c mice and their MHC-matched (BALB/c × DBA/2)F1 and F2 hybrids by systemic immunization with cartilage/intervertebral disk proteoglycan (PG). As in human ankylosing spondylitis, the MHC was the major permissive genetic locus in murine PG-induced spondylitis (PGIS). Two major non-MHC chromosome loci with highly significant linkage were found on chromosomes 2 (Pgis2) and 18 (Pgis1) accounting for 40% of the entire F2 trait variance. The dominant spondylitis-susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
11
0
3
Order By: Relevance
“…Because no other inbred strains have, as yet, been found to be susceptible to SpA (9,13,17), we believe that only a very few genes control SpA susceptibility, and that these genes are most likely the same in the BALB/c and C3H strains. The first genome-wide screening studies of 223 (BALB/c ϫ DBA/ 2)F 2 hybrid mice have been completed recently, and indeed, only 2 definitive loci (on chromosomes 2 and 18) and 4 suggestive loci (on chromosomes 11, 12, 15, and 19) seem to be linked to PGIS in this MHC-matched generation (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no other inbred strains have, as yet, been found to be susceptible to SpA (9,13,17), we believe that only a very few genes control SpA susceptibility, and that these genes are most likely the same in the BALB/c and C3H strains. The first genome-wide screening studies of 223 (BALB/c ϫ DBA/ 2)F 2 hybrid mice have been completed recently, and indeed, only 2 definitive loci (on chromosomes 2 and 18) and 4 suggestive loci (on chromosomes 11, 12, 15, and 19) seem to be linked to PGIS in this MHC-matched generation (23).…”
Section: Discussionmentioning
confidence: 99%
“…This observation may indicate that PGIS is a more uniform disease than PGIA. Indeed, although several genetic loci have been implicated in different forms of autoimmune/experimental arthritis (17,43) and in rheumatoid arthritis (43)(44)(45), only a very few, probably only 2 dominant, non-MHC loci (on chromosomes 2 and 18) have been identified that could control susceptibility to spondylitis in (BALB/c ϫ DBA/2)F 2 hybrid mice (23). Importantly, both of these 2 genetic loci correspond to those identified in human patients with AS (30,31,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…D'autres formes de SpA se sont déclarées chez des rongeurs transgéniques porteurs de l'HLA-B27 [21], ou chez la souris transgénique exprimant un collagène mutant de type IX ou une forme tronquée de TNF-␣ [28]. Dans cet article, en plus des données chez l'homme, nous discuterons de la spondylarthrite induite par les protéoglycanes (PGIS), un modèle murin autoimmun de SpA [29,30].…”
Section: Allèles Non Complexes Majeurs D'histocompatibilités (Cmh) Daunclassified
“…Although spondylitis correlated with onset and severity of peripheral arthritis in BALB/c mice, axial disease became independent of peripheral arthritis after the F2 generation. Linkage analysis showed that two spondylitis-related gene loci, pgis1 and pgis2, are linked to the axial disease in F2 mice [187]. Interestingly, combination of DBA/2-derived pgis1 and BALB/C-derived pgis2 result in the highest disease susceptibility.…”
Section: -55 Il-23 Il-17 or Il-22 Overexpressionmentioning
confidence: 99%
“…Interestingly, combination of DBA/2-derived pgis1 and BALB/C-derived pgis2 result in the highest disease susceptibility. The loci include many genes related to immune responses, such as the IL-1 family gene cluster that had been reported in AS [187].…”
Section: -55 Il-23 Il-17 or Il-22 Overexpressionmentioning
confidence: 99%